PROBLEMS OF LAW ENFORCEMENT AGAINST PERPETRATORS OF PRODUCTION AND DISTRIBUTION OF OPLOSAN IN EAST JAVA REGIONAL POLICE - Suroso, Dr. Imam; Jamil, Dr.; Razak, M. Abdul; Ramadhina, Nabila Fitra (jfpublisher, 2024)
The low purchasing power and high cost of legal alcoholic beverages in Indonesia has led to an increase in the demand for locally produced oplosan (mixed) alcoholic beverages. This phenomenon is a serious concern for law enforcement officials, particularly in the East Java Regional Police, considering the significant increase in the manufacture and distribution of oplosan. Despite this, the sale of legal alcoholic beverages remains quite common and high. This research aims to identify the various challenges faced by law enforcement in prosecuting perpetrators responsible for the production and distribution of oplosan. Using empirical research methodology and in-depth interviews with law enforcement officials at the East Java Regional Police, this research revealed significant difficulties in enforcing the law against this illegal practice. The findings of this research revealed that consuming illegal alcoholic beverages, such as oplosan, poses a high health risk to the people who consume them. Strict laws on alcohol consumption and the low price of oplosan have led to an increase in its sale. The production and distribution of oplosan is regulated by criminal law in Indonesia, with severe sanctions for violators. Despite the legislative framework aimed at protecting the public, law enforcers in the East Java Regional Police face obstacles, such as geographical factors, the common drinking culture, economic issues, and the lack of consequences for violators.